Analisis Spasial Penentuan Lokasi Jalan Tol Di Daerah Istimewa Yogyakarta Menggunakan Teknologi Penginderaan Jauh Dan Sistem Informasi Geografis - Wibawa, Rasyid Fajar, Agus Anggoro Sigit, S. Si, M. Sc (2016)
This research is the application of techniques of remote sensing and geographic information systems are used for the determination of the location of the toll road. As for the purpose of this research is to determine the suitability of the land for the spatial location of the line the highway in the area of research, as well as analyzing the spatial keruangan of land suitability for location of highway line in the area of research so that it can be known to the most suitable land for the location of the highway. The methods used in this research is the remote sensing and geographic information systems. The utilization of remote sensing data is used to assist in data collection parameters the suitability of land for roads, as well as keterlintasan is used for validation of the data by means of direct observation by using a sample. Quantitative approach i.e. do the analysis by utilizing geographic information Systems technology with engineering pengharkatan (secoring) variable determining the suitability of land for toll road served in spatial in the form of a map, as well as overlay techniques performed on the maps of the determining variables suitability of land for toll road location, resulting in a map the suitability of land for highways. The research results showed that: (1) Suitability of land utntuk the location of the highway consists of 4 levels of land suitability class i.e. class I (very appropriate), II (accordingly), III (Moderate) and class IV (less fit). Land suitability class I (very appropriate) has an area of 395.29 km2 or 13% of the whole area of research, land suitability for class II (fit) has an area of 1,448.02 km2 or proposi extents 46%, while for class III (moderate) the extent of 1,222.10 km2 or 39% of the whole area of research, and for class IV (less appropriate) has an area of 94.45 km2 or 3% proposi luasannya. (2) the spatial suitability of land for toll road lanes locations based on a unit of land in the area of research, retrieved the following spatial, land suitability class I found on 24 units of land, land suitability for class II unit 58 is present on the land, and the land suitability class III contained on 58 units of land, and land suitability class IV there are 19 units on land.